Variação do canto de Thamnophilus Doliatus (Linnaeus, 1764) (Aves: Thamnophilidae) em diferentes regiões da América Latina - Catalano, Ana Luiza Camargo [UNESP] (2015)
The aim of this study was to analyze and to compare vocalizations of individuals of the species Thamnophilus doliatus from different locations of Latin America. 280 loudsongs from 140 individuals were analyzed and the variables taken into account were the following: number of notes, duration of the sequenced patch, note rate (notes per second), overall peak frequency, duration of the terminal note, and peak frequency of the terminal note. The loudsongs were also divided into portions in order to measure the variation of note rate (speed) and pitch (frequency) along the patch. The loudsong characteristics were correlated with geographic factors such as latitude, longitude and altitude to check if there is any acoustic pattern with the location. Also, the sample was clustered into subspecies for comparisons. The analyzed variables were strongly correlated with latitude, where individuals from equatorial locations had loudsongs with more notes, longer in duration, faster in note rate and a terminal note lower in peak frequency. The variables also appeared to be significantly correlated with longitude, including as well the overall peak frequency. Seven subspecies were identified according to their locations, however, only five of them were used for comparisons. Results showed a separation of the intermedius and radiatus subspecies due to their significant divergence in number of notes, patch duration, note rate and peak frequency. Comparisons with the recently separated species Thamnophilus capistratus were also made and no significant variation were found in the number of notes and total duration, but there were differences in note rate, overall peak frequency, peak frequency and duration of the terminal note. Because song characteristics between the different species (T. doliatus and T. capistratus) presented to be more similar than among the subspecies of T. doliatus, raises the question of the existence of more than one species within ...